PENINGKATAN PEMAHAMAN PESERTA DIDIK PADA MATA PELAJARAN PPKN DI KELAS VIII.2 MELALUI MODEL PEMBELAJARAN PROBLEM-BASED INSTRUCTION SMP NEGERI 10 PALAEMBANG - Sri Artati Waluyati; Reni; Mukti Rahayu; Gusmer, Puja Rahmanu; Meliyani; Maya Astra Cibro; Naufal Najib (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research is motivated by the existence of problems in PPKn learning, marked by students not being able to meet several indicators of learning comprehension. On the other hand, teachers still apply conventional learning methods, namely lectures. The lecture method commonly used by teachers is less efficient in its application so that it does not arouse students' interest in boring learning. As a result, students do not fully understand the subjects they are studying. The purpose of this study is to improve students' learning comprehension abilities towards PPKn learning by implementing the pair checks learning model in class VIII.2 of SMP Negeri 10 Palembang. The design of this study is based on classroom action research carried out by a teacher in the classroom. The action plan in each cycle of this research is grouped into four stages, namely: 1. Planning stage, 2. Action implementation stage, 3. Observation/observation stage, 4. Reflection. Research data were obtained through test sheets and documentation. The success criteria determined in the study were 60%. The results of the study showed that in cycle I the level of students' understanding ability increased from the original 40% to 50% but the success criteria set had not been met. Improvements were made in cycle I to continue cycle II which increased by 11% to 61% which means that the intervention was declared successful because it achieved the success set. The success of this study was achieved through improvements made in each cycle.